Pengaruh Penggunaan Booklet pada Konseling Gizi Terhadap Perubahan Pengetahuan Pasien Diabetes Mellitus di RSUP Dr. M. Djamil Padang Tahun 2017 - IswanelIy Mourbas; Novelasari Novelasari; Mulyatni Nizar (Poltekkes Kemenkes Padang, 2018)
Research in 2012 at Dr. Hospital M. Djamil Padang leftovers from 66.0% of patients treated (Mourbas, 2012), the 2016 study of the patient's remaining food was 23.4%. This figure exceeds the restriction of food leftovers based on nutritional MSS in hospitals <20%. The high number affects the healing of Diabetes Mellitus patients. This study aims to determine the effect of booklet use in nutritional counseling on changes in knowledge of Diabetes Mellitus patients in Dr. Hospital. M.Djamil Padang. This type of research is a quasi-experiment experiment designed by Two Group Pretest Postest Design, a sample of 42 people for 2 research groups. Knowledge data by interview method, questionnaire, measured before and after nutrition counseling was given. The analysis was done by univariate and bivariate using different T test 2 dependent and independent mean with a confidence level of 95% (α = 5%). The results of the study were 66.7% - 81.0% of respondents had good knowledge. in the group that received counseling with a booklet after being given counseling (81.0%), the average value of knowledge was higher in the booklet group compared to the group without the booklet both before and after counseling. The results of the independent T-test obtained no differences in knowledge in the two counseling groups (p> 0.05) both before and after counseling. The conclusion is that nutritional counseling using booklets does not affect changes in knowledge but can increase knowledge about DM disease.